2013
DOI: 10.1111/exd.12147
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of hyaluronan synthase and hyaluronidase mRNA may affect hyaluronic acid distribution in keloid disease compared with normal skin

Abstract: Keloid disease (KD) is a fibroproliferative disorder characterised partly by an altered extracellular matrix (ECM) profile. In fetal scarring, hyaluronic acid (HA) expression is increased, but is reduced in KD tissue compared with normal skin (NS). The expression of Hyaluronan Synthase (HAS) and hyaluronidase (HYAL) in KD and NS tissue were investigated for the first time using a range of techniques. Hyaluronan synthase and HYAL mRNA expression were significantly increased in NS tissue compared with KD tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…HAS and HYAL activities are also reduced in keloids, supporting the earlier observations . Hypertrophic scars also have decreased HA deposition, particularly in the papillary dermis, but intermediate between that of normal scars and that of keloids …”
Section: Other Aspects Of Hyaluronan Metabolism In Wound Healingsupporting
confidence: 85%
“…HAS and HYAL activities are also reduced in keloids, supporting the earlier observations . Hypertrophic scars also have decreased HA deposition, particularly in the papillary dermis, but intermediate between that of normal scars and that of keloids …”
Section: Other Aspects Of Hyaluronan Metabolism In Wound Healingsupporting
confidence: 85%
“…We found that a gradation in increasing epidermal thickness correlated with the degree of severity of the scar: epidermal-thickness keloid > hypertrophic scar > normotrophic scar > normal skin. In the literature, the keloid epidermis has been described as both appearing morphologically normal 1,2,26,33 and having increased thickness, 14,[34][35][36][37][38] while some found a thicker epidermis in both abnormal scars, 31,39,40 and yet others considered a thicker epidermis to be an inconsistent finding. 28,41 However, to date we have not found a publication comparing and measuring the epidermal thickness of sufficiently matured scars (≥ 1 year old) of the entire scar spectrum in a standardized, quantifiable manner.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to skin 21 , intestine 22 , cartilage 23 , and other tissues is accompanied by inflammation and changes in HA accumulation, resulting from concurrent increased synthesis of HA itself and HA-associated proteins, such as TSG6 (encoded by Tnfaip6 ), the heavy chains of inter-alpha-trypsin inhibitor (encoded by Itih1–5 genes), and pentraxin.…”
Section: Resultsmentioning
confidence: 99%